The HB-6, CDw75, and CD76 differentiation antigens are unique cell- surface carbohydrate determinants generated by the beta-galactoside alpha 2,6-sialyltransferase (The Rockefeller University Press, 1992)
Expression of the beta-galactoside alpha 2,6-sialyltransferase (alpha 2,6-ST) was shown to regulate the generation of multiple cell-surface differentiation antigens (Ags) that may be necessary for lymphocyte function. A new mAb was produced, termed HB-6, that was shown to identify a novel neuraminidase-sensitive cell-surface Ag expressed by subpopulations of human lymphocytes and erythrocytes. In attempting to isolate a cDNA encoding the HB-6 antigen by expression cloning, a cDNA encoding the alpha 2,6-ST (EC 2.4.99.1) was obtained. Since expression of the alpha 2,6-ST protein was shown to be limited to the Golgi apparatus, the cell-surface HB-6 Ag was demonstrated to be the product of alpha 2,6-ST activity. Interestingly, alpha 2,6-ST expression also generated two other neuraminidase-sensitive lymphocyte cell-surface differentiation Ags, CDw75, and CD76. The HB-6, CDw75, and CD76 mAb identified distinct Ags that were differentially expressed by different B cell lines and exhibited different patterns of expression in tissue sections. These results indicate that alpha 2,6-ST expression is a critical regulatory step in the formation of the Ags that are recognized by these mAb, and that an alpha 2,6-linked sialic acid residue is an essential component of each Ag. Thus, expression of a single ST can result in the generation of multiple distinct antigenic determinants on the cell surface which can be distinguished by mAb and may have regulatory roles in lymphocyte function.